2011
DOI: 10.1002/art.30381
|View full text |Cite
|
Sign up to set email alerts
|

Associations between salivary gland histopathologic diagnoses and phenotypic features of Sjögren's syndrome among 1,726 registry participants

Abstract: Objectives The Sjögren’s International Collaborative Clinical Alliance (SICCA) is an ongoing NIH-funded registry whose cohort ranges from those with symptoms of possible Sjögren’s syndrome (SS) to those with obvious disease. Using this database we examined associations between labial salivary gland (LSG) histopathology and other phenotypic features of SS. Methods LSG biopsy specimens from SICCA participants underwent protocol-directed histopathological assessments. Among 1726 LSG specimens exhibiting any pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
249
1
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 256 publications
(279 citation statements)
references
References 60 publications
6
249
1
12
Order By: Relevance
“…Taking into account the pivotal role of GCs in driving B-and Tcell activation, it has been suggested that their presence in the pSS glandular infiltrates may affect the clinical picture and the progression of the disease in several ways [57]: (i) the higher degree of lymphocytic organization may lead to a more pronounced disruption of glandular architecture and secretory function impairment [31,58]; (ii) GC formation may increase lymphocyte activation and function, autoantibody production [57], and immune complex formation, leading to extraglandular manifestations [57][58][59]; and (iii) the development of B-cell NHL seems to rely on antigen-driven stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the pivotal role of GCs in driving B-and Tcell activation, it has been suggested that their presence in the pSS glandular infiltrates may affect the clinical picture and the progression of the disease in several ways [57]: (i) the higher degree of lymphocytic organization may lead to a more pronounced disruption of glandular architecture and secretory function impairment [31,58]; (ii) GC formation may increase lymphocyte activation and function, autoantibody production [57], and immune complex formation, leading to extraglandular manifestations [57][58][59]; and (iii) the development of B-cell NHL seems to rely on antigen-driven stimulation [60].…”
Section: Discussionmentioning
confidence: 99%
“…Specimens from SS patients demonstrated characteristic features of SS, including a salivary gland pathological focus (SGPF) score of ≥1 and presence of lymphoepithelial lesions (16), whereas specimens obtained from the control subjects did not present such features. Subsequently, SS patients were divided into two groups based on their SGPF scores, as follows: Scores of <3 (n=16) and scores of ≥3 (n=12) (17).…”
Section: Methodsmentioning
confidence: 99%
“…The histological hallmark is a focal lymphocytic infiltration of the exocrine glands, determined by minor salivary gland biopsy (MSGB). [1][2][3][4][5] The incidence of pSS is 0.3-0.7% in China, 6 and there were more female patients than male patients. At present, it is still difficult to establish the diagnosis of pSS because of lack of specific symptoms and laboratory markers.…”
Section: Introductionmentioning
confidence: 99%